Toxicity of herbal medications suggested as treatment for COVID‐19: A narrative review - Michael A. DiPietro; Christopher Mondie (Journal of the American College of Emergency Physicians Open)
Abstract Objectives In the absence of a definitive cure, herbal medications are gaining increasing popularity in the general public for treatment of coronavirus disease 2019 (COVID‐19). Although many herbal preparations are safe and can be used without complication, serious toxicities do occur. This article focuses on the major characteristics and toxicities of herbal preparations that have been proposed as treatments for COVID‐19. Methods A review was performed focusing on herbal preparations that have gained popularity as potential treatments for COVID‐19. Some of these preparations have been directly recommended by government agencies, whereas others have gained popularity through various other news sources. Results The herbal preparations covered in this paper include the cardiac glycoside oleandrin, plants of the Datura genus, and herbs commonly used in traditional Chinese Medicine including plants of the Aconitum genus, bitter apricot seeds, ephedra, and licorice root. Conclusion Although herbal preparations have been reported to aid in the treatment of COVID‐19 with success, few clinical trials have been performed to evaluate their efficacy and instead rely mainly on in vitro studies and anecdotal reports. Furthermore, many of the herbal preparations suggested carry significant toxicities, and frontline healthcare workers should be aware of the common symptoms and toxidromes that result from these poisonings.